Repetitively pulsed operating regime of a high-pressure atomic xenon transition laser - Alekseev S. B.; Koval N. N. Nikolay Nikolaevich; Orlovskii V. M.; Skakun V. S.; Tarasenko V. F. Victor Fedotovich; Tolkachev V. S.; Fedenev A. V.; Shulepov M. A.; Shchanin P. M. (2004, 2004)
Title screen